The New European Security System - Roles Shifting and Renewal of Tasks - Rahmouni, Fatahennour (Journal of Legal Studies and Researches, 2021)
Achieving security and stability in the international system is one of the most important issues of international politics. However, the issue of consensus about mechanisms and ways to achieve it raises a great controversy and divergence between the actors in the international system and building regional security systems is the most adopted mechanism in this context. the Organization for Security and Co-operation in Europe and the North Atlantic Treaty Organization, and these two organizations have already succeeded in building the pillars of European security and clearly developing the interests of the state.